Head catechist Solomon Boassen and wife, Angmagssalik. Photo used in 1937 : Overkateket Salomon Boassen og hustru, Angmagssalik. Foto anvendt 1937 - Unknown (University of Southern California Digital Library (USC.DL), 2015)
Head catechist Solomon Boassen and wife, Angmagssalik. Photo used in 1937